Lady Macbeth and Us. Power, Body and Desire - Tiziana de Rogatis (Between, 2013)
Aim of the study is to analyze some traits of the women’s identity  as they emerge during the Early modern age. The analysis is focused on some passages from Macbeth, the Shakespeare’s play, related to the metamorfical and absolute (both feminine and masculine) figure of Lady Macbeth. The study proceeds in the analysis going through the close reading and to the psychoanalitic interpretation and, besides, to  the hystorical reconstrution of the visibile figures (especially Elizabeth I), which have inspired the Lady Macbeth’s figure and her crossing the genders